Programa de treinamento sobre a intervenção terapêutica relaxamento, imagens mentais e espiritualidade (rime) para re-significar a dor espiritual de pacientes terminais - Elias, Ana Catarina Tavares de Araújo (2005)
In tbis essay of Mastership we developed the study of the Therapeutical Intervention “Relaxation, Mental Images and Spirituality” (RIME) applied for terminal patients. The continuity for the research in the Doctorship consisted in operating a Course of Capadtance on the RIME Intervention usage by the health area professionals (Phasel) and on the analysis of the living experiences of these professionals in the application and evaluation of the RIME use in the patients (Phase2). The participants were a nurse, a female doctor, three psychologists and an altemative volunteer therapist, all experienced ones or scholars at Palliative Cares, they were selected by invitation and were in charge of caring of eleven terminal outpatients in public hospitais of Campinas, Piracicaba and São Paulo. This study had as a theory methodological base the Action-Research and the Phenomenology. The qualitative results were caught through the Semi-Structured Interview, the Structural Questionnaire and the Diary, and they were analyzed by the Contents Analysis method through the Thematically Analysis techniques. It is descriptive through the data, which were caught by the Analogical Visual Scale instrument of Welfare-AVS, in-color faces model, by using the Wilcoxon test. In the analysis of the professionals experiences were found five categories and fifteen sub-categories. In the analysis of the Spiritual Pain constitution, six categories were found with eleven sub-categories. In the application of the RIME was observed statistically expressive difference (p<0,0001) that is, at the end of each session the patients reported a greater levei of welfare than at the beginning, indicating that the RIME favors the re-signification of the Spiritual Pain in the terminal patients. The purposed training program showed itself effective in preparing health area professionals for the use of the RIME Intervention, qualifying them to care and give spiritual assistance inside an academic perspective.